2003
DOI: 10.1093/ndt/18.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant hyperglycaemia: a study of risk factors

Abstract: Persistent abnormal glucose tolerance after transplantation was seen in 45% of the patients. Pre-transplant factors including greater age, abnormal glucose tolerance parameters, and rapid gain in dry weight on HD, along with higher prednisolone and CsA doses early post-transplant were the important factors associated with the development of PTDM. Identification of patients with pre-transplant risks might allow modification of post-transplant immunosuppression with non-diabetogenic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 24 publications
3
32
1
2
Order By: Relevance
“…Van Hooff et al [17] evaluated the mechanisms of NODAT and concluded that CsA and tacrolimus tend to reduce insulin release, while concomitant use of corticosteroids increases insulin resistance. A dose-response relationship between corticosteroids and NODAT has been demonstrated in some studies [17,18] but not in others [19,20]. In our study, differences in mean steroid and CsA doses (mg/kg/day) in the first 3 months were not statistically significant between groups.…”
Section: Discussioncontrasting
confidence: 72%
“…Van Hooff et al [17] evaluated the mechanisms of NODAT and concluded that CsA and tacrolimus tend to reduce insulin release, while concomitant use of corticosteroids increases insulin resistance. A dose-response relationship between corticosteroids and NODAT has been demonstrated in some studies [17,18] but not in others [19,20]. In our study, differences in mean steroid and CsA doses (mg/kg/day) in the first 3 months were not statistically significant between groups.…”
Section: Discussioncontrasting
confidence: 72%
“…Age was also a factor in a retrospective study of 939 kidney transplant recipients wherein PTDM increased mortality in those less than 55 years of age, but not in those over 55, compared to non-PTDM (141). Awareness of the potential impact of post-transplant diabetes increased even more with the study by Cosio et al (142), who described a 2-fold increase in mortality (Figure 4) compared to nontransplant recipients, which was equal to that of pretransplant diabetes, already established to worsen outcome, and independent of other factors known to reduce survival, and was confirmed by Kaskiske et al and others (33,34,142,143). The reduction in patient survival due to PTDM is largely attributable to increased cardiovascular disease events (33), as much as 3-fold even when controlling for other risk factors (144 -146).…”
Section: B Kidney Transplant Outcomesmentioning
confidence: 79%
“…Corticosteroids are well established to cause hyperglycemia through several mechanisms: by inducing or worsening pre-existing insulin resistance, increasing hepatic gluconeogenesis, and long-term, by stimulating appetite and weight gain (33)(34)(35). The impact is dose-dependent.…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 99%
“…In another study, by taking a screening FBG level of 99 mg/dl (5.5 mmol/L) as a threshold for performing an OGTT, 90% of patients with newly diabetes and 78% of patients with dysglycemia were detected (38). In RTR, although 2HBG has been used to assess both the prevalence of PTD and IGT and changing glucose tolerance over time (1,22,40,41), no studies to date have examined the relationship between FBG and 2HBG. In this study, the FBG that gave the optimal sensitivity and specificity for predicting PTD was 101 mg/dl (5.6 mmol/L).…”
Section: Relationship Between Fbg and 2hbg In Rtrmentioning
confidence: 99%